The form of the poem in the granadian era - خضر رامي (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The two-and-a-half-year-long Granada period produced the experiences of poets who contributed to the building of the literary and cultural civilization of Granada and wrote to witness the decline of that civilization when Granada fell in 1994. Although the Andalusian poem has received many studies, the study of the structure of the poem in the era of the children of the Red has not received sufficient attention. It should be noted that Moroccan and Oriental studies have provided rich material in the study of the ancient text , And these studies focused on the study of the experiences of specific poets, did not meet all the poets at that stage, and from here we should try to study the structure of the poem at that stage. It should be noted that the studies that dealt with the study of the term of building the poem are few studies, and that the most studies tend to study the term (structure poem), and the most important poets of this period: Ibn Sahl - Ibn Farkun - Ibn Abar - Joseph III - Abu Hayyan - Karim al-Qaisi - Ibn Zmrk - Ibn al-Ghamaz - Qasim bin Abdullah al-Balansi - Ibn Hobeish - Ibn al-Janan - Al-Fazazi - Abdul Karim al-Basti - Ibn al-Khatib